A metapopulation model to simulate West Nile virus circulation in Western Africa, Southern Europe and the Mediterranean basin - (:unkn) unknown (My University, 2010)
In Europe, virological and epidemiological data collected in wild birds and horses suggest that a recurrent circulation of West Nile virus (WNV) could exist in some areas. Whether this circulation is permanent (due to overwintering mechanisms) or not remains unknown. The current conception of WNV epidemiology suggests that it is not: this conception combines an enzootic WNV circulation in tropical Africa with seasonal introductions of the virus in Europe by migratory birds. The objectives of this work were to (i) model this conception of WNV global circulation; and (ii) evaluate whether the model could reproduce data and patterns observed in Europe and Africa in vectors, horses, and birds. The model was calibrated using published seroprevalence data obtained from African (Senegal) and European (Spain) wild birds, and validated using independent, published data: seroprevalence rates in migratory and resident wild birds, minimal infection rates in vectors, as well as seroprevalence and incidence rates in horses. According to this model, overwintering mechanisms are not needed to reproduce the observed data. However, the existence of such mechanisms cannot be ruled out.
Keywords: African Research